SISTEM REKOMENDASI DESTINASI WISATA DI KABUPATEN TIMOR TENGAH SELATAN MENGGUNAKAN METODE SOM (SELF ORGANIZING MAP) - selan, frederikus; Yampi R. Kaesmetan (Jurnal Publikasi Manajemen Informatika, 2026)
The recommendation system for natural tourism destinations in South Central Timor Regency uses the Self-Organizing Map method. As an area with diverse natural tourism potential but has not been optimally explored, South Central Timor requires an innovative approach to increase the visibility of its tourist destinations. This website-based system integrates various important parameters such as natural characteristics, accessibility, facilities, tourist experience, temporal factors, costs, and sustainability aspects to produce personalized recommendations for tourists. The Self-Organizing Map method was chosen because of its ability to group tourist destinations based on similar characteristics without requiring previous data labels, and can identify hidden patterns that may not be visible in conventional analysis. The Final Project shows that the implementation of this recommendation system not only improves the tourist experience through personalization, but also encourages a more even distribution of visits to various tourist destinations in South Central Timor, supports the local economy, and promotes sustainable tourism practices. The development of the system in website format provides advantages in terms of accessibility, ease of content updates, rich multimedia integration, and optimization for search engines. This research makes a significant contribution to the development of technology-based tourism in areas with tourism potential that has not been maximally exposed.